Does Lin28 Antagonize miRNA-Mediated Repression by Displacing miRISC from Target mRNAs? - Kallen, Amanda N.; Ma, Jing; Huang, Yingqun (Frontiers in Genetics, 2012)
Lin28 is a developmentally regulated RNA-binding protein that plays important roles in diverse physiological and pathological processes including oncogenesis and brain synaptic function. These pleiotropic roles of Lin28 are mechanistically linked both to its ability to directly stimulate translation of genes involved primarily in cell growth and metabolism and to its ability to block biogenesis of a subset of miRNAs including the let-7 family of miRNAs. In the case of direct stimulation of gene expression, Lin28 binds to targeted mRNAs through recognition of Lin28-responsive elements (LREs) within mRNAs and recruits RNA helicase A (RHA) to promote translation. RHA belongs to the DEAD-box protein family of RNA helicases, which generally catalyze ATP-dependent unwinding of RNA duplexes or remodeling of ribonucleoprotein complexes (RNPs). Since any given mRNA can potentially be inhibited by miRNAs bearing complementary sequences, we hypothesize that binding of Lin28 to LREs not only nucleates the binding of multiple Lin28 molecules to the same mRNA, but also leads to remodeling of RNPs through recruitment of RHA and causes release of inhibitory miRNA-induced silencing complexes (miRISCs) bound to the mRNA. This mode of action may contribute to Lin28-mediated stimulation of translation in both tumor and neuronal cells.